Reconstruction of the Neziraga Mosque Complex in Mostar - Pašić, Amir, 1953-2022 (My University, 1999)
The historical Neziraga Mosque in Mostar, Bosnia and Herzegovina was restored and inaugurated within the framework of IRCICA's Mostar 2004 program with the generous donation by H.H. Sheikh Drr. Sultan Bin Mohamad Al-Qassimi, the Ruler of Sharjah. A ceremony was held in Mostar on September 10, 1999 to mark the opening of the Mosque.
Rekonstrukcija Kompleksa Nezir-Agine Džamije u Mostaru
There is humming and intermittent gaps in the recording.
Detailed information about the reconstruction of the Neziraga Mosque Complex and also other mosques in Bosnia and Herzegovina can be found in the following publications: Pašić, Amir (2006). Historic reconstruction of the Neziraga Mosque Complex in Mostar, Bosnia and Herzegovina. İstanbul: IRCICA. (IRCICA Library call no. 726.20949742 PA.H) Eren, Halit; Pašić, Amir and Zgonić, Aida Idrizbegović (2013). Restoration of Mosques in Bosnia and Herzegovina. İstanbul: IRCICA. (IRCICA Library call no. 726.20949742 ER.R)
CD created from the original video.
Keywords: Mostar 2004; Neziraga Mosque Complex-Mostar; Architecture-Bosnia and Herzegovina; Mosques-Bosnia and Herzegovina